Improving communication to tackle obesity in the UK. - Jebb, SA; Lang, R; Penrose, A (2003)
Obesity is a serious health issue. In the UK the prevalence of obesity has trebled in the last 20 years and today one in five adults is clinically obese. Research shows that obesity is a predictable response to an environment that favours the consumption of energy-dense foods and allows minimal physical activity. This finding implies that the efficacy of public health messages to individuals to inform their lifestyle choices will be enhanced by environmental changes that support and facilitate healthy options. The present paper focuses on the importance of communicating scientific knowledge to the stakeholders with a responsibility for tackling obesity and addresses some of the barriers that are encountered.